TH5.8 Use of Botulinum Toxin A infiltration in conjunction with negative pressure wound dressing and mesh-mediated traction in the management of the 'open abdomen'. (9th August 2022) - Mohamed, Imran; Egeler, Christian; Ford, Simon; White, Thomas; Harris, Dean; Harries, Rhiannon
Abstract: Aims: Botulinum Toxin A (BTA) is widely used in complex abdominal wall reconstruction (CAWR). It temporarily paralyses the oblique muscles allowing medialisation of the rectus sheath and decreases tension on the closure. This analysis presents the use of BTA in management of the 'open abdomen' (OA). Methods: Retrospective series of patients with OA where BTA was used in conjunction with Abthera TM negative pressure wound therapy (NPWT) and polypropylene mesh-mediated traction (MMT) to attempt fascial closure. BTA was performed by Anaesthetists with experience of BTA use in CAWR using Dysport® 600 IU. Results: We include 5 patients since 2020. Median age at index operation was 55 years (range 39–81); four were male. Index operations were intra-abdominal catastrophe where fascia closure impossible (n=2), dehiscence after Vertical Rectus Abdominis Myocutaneous (VRAM) flap for pelvic malignancy (n=2) and colectomy for obstructing colorectal cancer complicated by rectus sheath necrotising fasciitis (n=1). There were no immediate complications from BTA infiltration. All patients achieved primary fascial closure with a median of five re-looks (range 3–7). There were no full-thickness dehiscences after final closure. One patient died within 1 month from unrelated cause. One patient had no clinically palpable incisional hernia at six months and a further two had no incisional hernia at six and 12 months, respectively, on cancer surveillance CT. Conclusion: BTA in the setting of the OA in conjunction with NPWT and MMT appears safe and effective in achieving fascial closure, and can potentially reduce the risk of incisional hernia. Further studies are welcomed.